Talking in a language that everyone can understand? Clarity of speeches by the ECB Executive Board - Alexander Glas; Lena Müller (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
We use data on speeches held by members of the European Central Bank's (ECB) Executive Board to analyze whether clarity of central bank communication has increased over time. Employing readability measures as proxy variables, we find that clarity of information provision is trending upward since the inception of the ECB. The increase is gradual, rather than being induced by changes in the board composition or major macroeconomic events. Clarity is higher for speeches aimed at general audiences and for speeches by female speakers. We also show that media sentiment about the ECB is negatively related to complexity.
Keywords: E52; E58; 330; Central Bank Communication; Monetary Policy Transparency; Clarity; Readability